Herr-complexes in the Lubin-Tate setting - Kupferer, Benjamin; Venjakob, Otmar (Mathematika, 2022)
In this article, we extend work of Herr from the case of cyclotomic (φ,Γ)$(φ ,Γ )$-modules to the general case of Lubin-Tate (φ,Γ)$(φ ,Γ )$-modules. In particular, we define generalized φ- and ψ-Herr complexes, which calculate Galois cohomology, when applied to the étale (φ,Γ)$(φ ,Γ )$-modules attached to the coefficients.